Spatial variation in risk factors for anti-hepatitis E antibody titers in a population-based German study - Díaz, Andrea C.; Ittermann, Till; Nauck, Matthias; Petersmann, Astrid; Völzke, Henry; Schauer, Birgit (Scientific reports, 2025)
The transmission of hepatitis E virus (HEV) genotype 3 remains unclear. Up to date, it is predominantly considered a foodborne disease. However, there is growing evidence that other transmission pathways exist. The aim of this study was to analyze risk factors for anti-HEV IgG titers in the Study of Health in Pomerania, a population-based cohort located in Northeast Germany. We performed cross-sectional analyses using quantile and logistic regression. Spatial location was included as an interaction term to explore whether residential location of the participant acts as an effect modifier. The risk factors assessed were consumption frequency of meat, sausage, fish and raw vegetables, high-risk occupation and animal contact. The estimated seroprevalence of anti-HEV IgG was 27.3% (95% confidence interval [CI] 26.0%, 28.6%). Participants living in rural coastal areas had 14.5 U/ml higher antibody titers both for high meat (95% CI 3.9, 25.2; P = 0.008) and high sausage consumption (95% CI 4.1, 24.9; P = 0.006) in comparison with low consumption. In urban areas, participants who had contact with domestic carnivores had higher antibody titers (by 12.8 U/ml; 95% CI 0.3, 25.3; P = 0.046). Our results imply that risk factors of HEV exposure might differ among geographical regions. More research is needed to clarify the mechanisms underlying these findings.